Standing Still: The Implications of Clapper for Environmental Plaintiffs’ Constitutional Standing - Chin, Courtney (Columbia Journal of Environmental Law, 2019)
In 2013, the Supreme Court decided Clapper v. Amnesty International, denying standing to a group of human rights, labor, legal, and media organizations to challenge the constitutionality of a provision of the Foreign Intelligence Surveillance Act (“FISA”). Justice Alito, writing for a 5-4 majority, held that the respondents lacked standing because the alleged injury was not “certainly impending,” the injury was not fairly traceable to the FISA provision, nor were the costs incurred by the respondents fairly traceable to the FISA provision. Naturally, the four dissenters proposed an alternate view of the facts: Justice Breyer compared the likelihood of the respondents’ injury not occurring as similar to the chance that “despite pouring rain, the streets will remain dry (due to the presence of a special chemical).” He then criticized the majority, arguing that “certainty is not, and never has been, the touchstone of standing.” Although Clapper did not deal with issues of environmental law, it signaled a further heightening of standing requirements, prompting much discussion of the forecasted increased difficulty of proving standing in environmental litigation. Because standing is often a contentious issue in environmental litigation, some surmised that the Court’s use of the “certainly impending” standard for injury-in-fact—and its express rejection of the Second Circuit’s “objectively reasonable likelihood” standard—might shut the door on many more environmental plaintiffs at the standing stage. ... Contrary to this discourse, in this Note I argue that Clapper may not have as large an impact on standing for environmental plaintiffs as early commentators believed. Instead, the opinion is carefully constructed so as to reaffirm the major standing decisions before it, namely Lujan, Laidlaw, Massachusetts, and Summers. An important concession in footnote 5 of Clapper also leaves open the possibility that plaintiffs may demonstrate injury in fact based on a “substantial risk” of harm. Finally, as I will argue below, there is ample reason to believe that dismissing this suit was at least in part motivated by a desire to avoid more difficult and sensitive questions on the merits, which included constitutional claims and issues of national security and counterterrorism. Thus, this case is not a departure from the existing standing doctrine, and environmental plaintiffs need not strategize new ways of demonstrating standing.